Hydrodynamic performance of the dual-chamber oscillating water column device placed over the undulated sea bed. (April 2022) - Trivedi, Kshma; Koley, Santanu
Abstract: The present study analyzed the efficiency of the dual-chamber oscillating water column device placed over the undulated bottom. The efficiency of the device is studied for various shape parameters such as chamber lengths, the draft of the lip wall of the device, turbine damping coefficients, and ripples of the corrugated bottom. It is seen that the efficiency initially increases as the wavenumber increases. However, the efficiency of the device becomes lower for shorter incident wavelength. The amplitude of the resonance becomes higher for device having wider chamber. Similar higher resonance occurs when the turbine damping coefficients and the number of ripples of the corrugated bottom take higher values. An opposite pattern is formed with the variation in draft of the lip wall of the device. The draft of the outer chamber plays a dominant role in enhancing the efficiency as compared to the draft of the inner chamber of the device. Further, the efficiency becomes higher as the turbine damping coefficient takes the higher values.